Crowd-sourcing tools unlock insurance scaling, supporting an expansion to 230 villages in Ethiopia - CGIAR Research Program on Climate Change, Agriculture and Food Security (2020)
The International Research Institute for Climate and Society (IRI), supported by CCAFS, worked with the R4 Rural Resilience initiative in Ethiopia - a collaboration between the World Food Programme, Oxfam, and other partners - to build tools for participatory design of agricultural index insurance. These tools enabled local partners to make data-driven decisions about index insurance contracts on a scale both deeper - customized for each village - and wider - reaching a total 230 villages - than ever before.